Hamstrings mechanical properties profiling in football players of different competitive levels and positions after a repeated sprint protocol - Pimenta, Ricardo; Antunes, Hugo; Bruno, Paula; Veloso, A. P. (Frontiers in Physiology, 2024)
Purpose: This study compares the average speed, knee flexor peak torque and shear modulus of the hamstrings after a repeated sprint task, in football players of different competitive levels and playing positions.Methods: Fifty-four football field players without hamstring strain injury history participated, 15 being categorized as professional (2 nd league) and 39 as semi-professional (17 in 3 rd and 22 in 4 th league). Muscle shear modulus was assessed using ultrasound-based shear wave elastography at rest and at 20% of maximal voluntary isometric effort before and immediately after the repeated sprint protocol.Results: No significant differences were seen in average sprint speed between competitive levels (p = 0.07; η2p = 0.28) and positions (p = 0.052; η2p = 0.29). Moreover, the sprint fatigue index showed no significant differences between competitive levels (p = 0.14; η2p = 0.08) and playing positions (p = 0.89; η2p = 0.05). No significant differences were observed in hamstring shear modulus changes between competitive levels (p = 0.94; η2p = 0.03) and positions (p = 0.92; η2p = 0.03). Peak torque changes also showed non-significant association with competitive levels (p = 0.46; η2p = 0.03) and positions (p = 0.60; η2p = 0.02).The results of this study suggest that the average sprint speed performance parameter and mechanical parameters are not able to distinguish football players of different competitive levels and positions.